2007
DOI: 10.1007/s10067-007-0604-3
|View full text |Cite
|
Sign up to set email alerts
|

Accrual of organ damage over time in Argentine patients with systemic lupus erythematosus: a multi-centre study

Abstract: The goals of this study were to ascertain damage in patients with systemic lupus erythematosus (SLE) from five rheumatologic centres in Argentina and to examine overall damage, damage by domain and damage by item within each domain. We performed a retrospective observational study including patients with SLE (ACR 1997 revised and modified criteria) from five rheumatology centres in Argentina. Organ damage was scored using the SLICC/ACR DI (SDI), ascertained at years 1, 2, 5 and 10. Three centres provided infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 17 publications
0
11
1
2
Order By: Relevance
“…Taking in account the characteristics of the studied population, these findings are concordant with the pattern of organ damage accrual described by Gladman et al 9 However, in cohorts from a different ethnic background, renal and neuropsychiatric disease seem to be major contributors to damage. 8,15,16 In this study we demonstrated that the progression of damage in Portuguese SLE patients is associated with disease-related and therapyrelated factors. Damage accrual was significantly greater in older patients and in those testing positive for aPL antibodies.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Taking in account the characteristics of the studied population, these findings are concordant with the pattern of organ damage accrual described by Gladman et al 9 However, in cohorts from a different ethnic background, renal and neuropsychiatric disease seem to be major contributors to damage. 8,15,16 In this study we demonstrated that the progression of damage in Portuguese SLE patients is associated with disease-related and therapyrelated factors. Damage accrual was significantly greater in older patients and in those testing positive for aPL antibodies.…”
Section: Discussionmentioning
confidence: 59%
“…Taking in account the characteristics of the studied population, these findings are concordant with the pattern of organ damage accrual described by Gladman et al 9 . However, in cohorts from a different ethnic background, renal and neuropsychiatric disease seem to be major contributors to damage 8,15,16 …”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular damage in our cohort was less common (3.1%) although Asian SLE patients have been shown to develop less cardiovascular damage than those of other ethnicities . Most cardiovascular damage in our cohort consisted of pericarditis (1.6%) and angina (0.9%), while Chinese (10.7%) and Jewish (17.2%) people develop cardiovascular damage at a similarly high frequency as non‐Asians (10–16%) …”
Section: Discussionmentioning
confidence: 65%
“…Finally, the rate of change of damage was estimated based on conversion to an annual rate of change. This could result in an over‐ or underestimation of the actual rate of damage accrual, since the rate of change might not be constant but could increase with longer disease duration, as in patients with SLE (36).…”
Section: Discussionmentioning
confidence: 99%